Comparative evaluation of basin and drip systems of irrigation in rubber - Jessy M D; Jacob Sarah; Mathew M; Punnoose K I (Indian Journal of Natural Rubber Research, 1994)
An experiment was conducted in central Kerala to compare basin and drip systems of irrigation in rubber. Irrigation was given at two levels (30 per cent and 50 per cent of crop evapotranspiration) and the same quantity was applied in both basin and drip methods. Both methods showed wide variation with respect to root, salinity and moisture distribution. Irrigation enhanced the growth of rubber significantly, irrespective of the method.
Keywords: Hevea brasiliensis; Irrigation system; Kerala; Soil moisture